Flight Nurse’s Roles in Aeromedical Evacuation: A Case Study of Patients with Gastrointestinal Problems - Changyai , Khwanhathai; Mahaviriyotai, Kittiya (Journal of The Royal Thai Army Nurses, 2024)
Gastrointestinal (GI) disorders can be found in both medical and surgical aspects and the primary causes are correlated to chronic diseases and injuries. When vulnerable GI patients experience life-threatening threats, there could be a high risk of fatality. Aeromedical evacuation is the transportation of patients in both normal and emergency situations, with the aim of transferring them to another facility or hospital to receive proper treatment. The transition of patients at the right time possibly reduces severity and decreases mortality rate. However, barometric pressure changes during the flight directly impact digestive organs, consequently leading to worse conditions and undesirable complications in case of ill treatment. To provide adequate care for GI patients, the flight nurses should be knowledgeable about aviation physiology, stresses of flight, patient assessment, and care procedures before organizing the evacuation and during the flight. Practices of flight nurses should be implemented during aeromedical evacuation to prevent the effects caused by stresses of flight and provide good care along the flight.